2020
DOI: 10.1080/0960085x.2020.1740617
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency creep and shadow innovation: enacting ambidextrous IT Governance in the public sector

Abstract: The current push towards increased innovation within the public sector calls for new approaches to IT Governance. However, recent findings highlight the aim to avoid trade-offs between innovation and efficiency through organisational ambidexterity. This paper reports a case study of ambidextrous IT Governance in two large government agencies. According to the findings, ambidextrous IT Governance is enacted through two separate but interrelated mechanisms that emerge simultaneously. In terms of exploitation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 81 publications
(126 reference statements)
3
44
0
2
Order By: Relevance
“…Instead of treating digital as something that is separate and apart, as noted by Tekic and Koroteev (2019) in their "proud to be analog" strategy, organizations should aspire to find a means through which digital may be Figure 2 Strategies for digital recoupling j JOURNAL OF BUSINESS STRATEGY j integrated and fused with the existing business model of the organization, that is, recoupled. As argued by Magnusson et al (2020), this would call for increased pluralism in the manner in which digital transformation is managed and organized. We should accept the innate difference in the digital and aspire for integration rather than decoupling.…”
Section: Strategies Of Digital Recouplingmentioning
confidence: 99%
“…Instead of treating digital as something that is separate and apart, as noted by Tekic and Koroteev (2019) in their "proud to be analog" strategy, organizations should aspire to find a means through which digital may be Figure 2 Strategies for digital recoupling j JOURNAL OF BUSINESS STRATEGY j integrated and fused with the existing business model of the organization, that is, recoupled. As argued by Magnusson et al (2020), this would call for increased pluralism in the manner in which digital transformation is managed and organized. We should accept the innate difference in the digital and aspire for integration rather than decoupling.…”
Section: Strategies Of Digital Recouplingmentioning
confidence: 99%
“…Digital innovation is acknowledged as being associated with a new logic for the way in which innovation is governed and managed. However, normative findings in terms of how governance should be designed to facilitate a fruitful conciliation of the clash are still lagging (Nambisan et al, 2017(Nambisan et al, , 2019Cannaerts, Segers and Warsen, 2019;Magnusson et al, 2020). Empirical evidence of a bias Nambisan et al (2017) identify the conceptual elements of the governance of digital innovation.…”
Section: Precursory Findings and Theoretical Framing 21 Governing Digital Innovationmentioning
confidence: 99%
“…Arvanitis et al (2013) revealed that IT training (ITG relational mechanism) has a positive impact on both product/ service and process innovation. In the context of public sector, Magnusson et al (2020) argued that ambidextrous ITG, in terms of exploration and exploitation, increases public sector innovation capability over time. Hence, we posit the following hypothesis:…”
Section: Itg and Innovationmentioning
confidence: 99%
“…Although some studies have examined the impact of ITG mechanisms on ITG effectiveness and performance and also on organizational performance in PSOs of various countries, the majority of these studies have investigated the effect of individual mechanisms on ITG effectiveness (Ali & Green, 2007), the effect of critical success factors (CSFs) on ITG performance (Nfuka & Rusu, 2011), and effect of ITG mechanisms on IT and organizational performance (Tonelli et al, 2017). Moreover, some studies have explored the link between IT-enabled investments and innovation in public sector, but these studies have mainly focused on IT as a driver of innovation for promoting creativity, constancy, connectivity, and courage for long-term progress (Nemeslaki, 2014); the effect of Information Communication Technology (ICT) on process innovation (Lohmeier, 2013); and the effect of ambidextrous ITG, in terms of exploration and exploitation, on innovation and efficiency (Magnusson et al, 2020). Furthermore, some researchers have analyzed the influence of innovation on organizational performance in public sector, but these have emphasized on the influence of organizational innovation on organizational performance (Damanpour et al, 1989), the impact of service and process innovation on operational performance (Moreira et al, 2017), and the performance management as a mediator in the association between innovation and organizational performance (Walker et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation